ICTs in Rural India: User Perspective Study of Two Different Models in Madhya Pradesh and Bihar - Meera Tiwari and Uma Sharmistha (Science Technology Society 2008; 13; 233, 2008)
This article presents fi ndings of two user perspective studies on the impact of ICTs in rural India. It is based on fi eldwork conducted by the authors in Dhar district of Madhya Pradesh and Madhubani district of Bihar. The fi rst study examines the impact of a state-led ICT initiative. The second looks at the impact of an ICT initiative by a non-government organisation. The article identifi es issues critical to enhancing the accessibility of ICT services to the poorest rural households. A comparison is made between the two models in reaching the ICT services to the rural poor.